Basic statistics for the health sciences - Kuzma, Jan W. (McGraw-Hill, 2005)
The first introductory statistics text written specifically to make statistics accessible for health science students . Assuming no prerequisites other than high school algebra, the authors provide numerous examples from health settings, a wealth of helpful learning aids, as well as hundreds of exercises to help students succeed in the course.